Enhancing Global Health System Resilience and Sustainability Post-COVID-19: A Grounded Theory Approach - Darmadi Darmadi; Maria V. Mikhailova; Zahraa H. Al-Qaim; Evgeniy V. Kostyrin; Marina V. Vasiljeva; Zhanna R. Gardanova; Mikhail E. Kosov (Ital Publication, 2023)
Based on a grounded theory approach to healthcare professionals’ experience, this study conducted a qualitative assessment of new opportunities and provided a conceptual justification of forward-looking trends of global health system efficiency improvement and resilience toward universal health in the post-COVID-19 era. The data were collected through semi-structured interviews, while theoretical saturation was reached after 20 interviews with international experts in Global Health System Resilience (psychologists, nurses, and community health consultants). The data were analyzed using four coding stages: initial, focused, axial, and theoretical. The results showed that to achieve global health system resilience toward universal health and safety coverage in the post-COVID-19 era, it is required to develop a strategy including the support of healthcare professionals, which allows coping with the emotional and psychological impact of the pandemic. Moreover, opportunities for professional development and collaboration can enhance their resilience and adaptability during and after crises. The findings suggest factors of global health system resilience ranked using the AHP method. The present research provides a valuable insight into the significance of telemedicine, remote care, and ensuring the safety of the healthcare industry and patients as the most crucial factors for enhancing health system sustainability. This article provides new policy recommendations to ensure the long-term effectiveness and sustainability of health systems. Doi: 10.28991/ESJ-2023-07-06-011 Full Text: PDF